Multi-locus phylogenetic network analysis of Ampelomyces mycoparasites isolated from diverse powdery mildews in Australia and the generation of two de novo genome assemblies - Lauren Goldspink; Alexandros G. Sotiropoulos; Alexander Idnurm; Gavin J. Ash; John D. W. Dearnaley; Morwenna Boddington; Aftab Ahmad; Márk Z. Németh; Alexandra Pintye; Markus Gorfer; Hyeon-Dong Shin; Gábor M. Kovács; et al. (PLoS ONE, 2025)
The interactions between powdery mildews ( Ascomycota , Erysiphaceae ), obligate biotrophic pathogens of many plants, and pycnidial fungi belonging to the genus Ampelomyces , are classic examples of specific mycoparasitic relationships. These interactions are common and finely tuned tritrophic relationships amongst host plants, powdery mildews, and Ampelomyces mycoparasites wherever these organisms co-occur in the field. Selected Ampelomyces strains have already been developed as biocontrol agents of powdery mildew infections of some crops. In Australia, their study has received little attention so far. Only a single Ampelomyces strain, included in a whole-genome sequencing (WGS) project, was known from this continent. Here, we report the isolation of 20 more Ampelomyces strains from eight powdery mildew species in Australia. Multi-locus phylogenetic network analyses of all the 21 Australian Ampelomyces strains carried out in combination with 32 reference strains from overseas revealed that the Australian strains belonged to four molecular taxonomic units (MOTUs). All those MOTUs were delimited earlier based on Ampelomyces strains isolated in Europe, North America, and elsewhere. Based on the phylogenetic analyses, two Australian strains belonging to different MOTUs were selected for WGS. Long-read (MinION) and short-read (Illumina) technologies were used to provide genome assemblies with high completeness. Both assemblies have a bipartite structure, i.e., consisted of AT-rich, gene-sparse regions interspersed with GC-balanced, gene-rich regions. These new high-quality assemblies and evidence-based annotations are important resources for future analyses of mycoparasitic interactions to disentangle molecular mechanisms underlying mycoparasitism, possible new biocontrol applications, and naturally occurring tritrophic relationships.